2014
DOI: 10.4161/epi.29628
|View full text |Cite
|
Sign up to set email alerts
|

A novel cancer-germline transcript carrying pro-metastatic miR-105 andTET-targeting miR-767 induced by DNA hypomethylation in tumors

Abstract: Genome hypomethylation is a common epigenetic alteration in human tumors, where it often leads to aberrant activation of a group of germline-specific genes, commonly referred to as “cancer-germline” genes. The cellular functions and tumor promoting potential of these genes remain, however, largely uncertain. Here, we report identification of a novel cancer-germline transcript (CT-GABRA3) displaying DNA hypomethylation-dependent activation in various tumors, including melanoma and lung carcinoma. Importantly, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 42 publications
1
62
0
Order By: Relevance
“…15 The increasing amounts of data have shown that miRNAs can act as oncogenes or tumor suppressors and participate in cancer development and progression. 16,17 Studies on miRNAs and tumors started with large-scale screening of microarray to detect the differentially expressed miRs between tumor tissues and normal tissues aiming at developing new strategies in tumor diagnosis and treatment in clinic. [18][19][20] For instance, in human acute lymphocytic leukemia, the expression levels of miR-15a and miR-16-1 are decreased; 21,22 in lung cancer, let-7 is downregulated, whereas miR-17-92 is upregulated; 23 in Burkitt's lymphoma, expression level of miR-155 is increased; 24 in esophageal cancer, miR-103 and miR-107 expression levels are increased; 25 in liver cancer, miR-21 expression level is increased.…”
Section: Discussionmentioning
confidence: 99%
“…15 The increasing amounts of data have shown that miRNAs can act as oncogenes or tumor suppressors and participate in cancer development and progression. 16,17 Studies on miRNAs and tumors started with large-scale screening of microarray to detect the differentially expressed miRs between tumor tissues and normal tissues aiming at developing new strategies in tumor diagnosis and treatment in clinic. [18][19][20] For instance, in human acute lymphocytic leukemia, the expression levels of miR-15a and miR-16-1 are decreased; 21,22 in lung cancer, let-7 is downregulated, whereas miR-17-92 is upregulated; 23 in Burkitt's lymphoma, expression level of miR-155 is increased; 24 in esophageal cancer, miR-103 and miR-107 expression levels are increased; 25 in liver cancer, miR-21 expression level is increased.…”
Section: Discussionmentioning
confidence: 99%
“…In melanoma cell lines, it has been shown that miR-767 can function as a regulator of cellular 5-hmC levels via targeting of TET genes, but miR-767 has exhibited a preferential effect on TET1. 37 Although there is are data concerning mechanism of TET's expression regulation in endometrial cancer, it is known that deregulation of some of these miRNAs, that is, miR-101 and miR-22, are associated with endometrial carcinogenesis. [38][39][40] Our results for the first time suggest that decreased mRNA expression of TET1 correlates with tumor progression and may serve as a potential prognostic biomarker in endometrial cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of miR-494 in HCC cells leads to epigenetic silencing of invasion suppressing miRNA genes through inhibition of DNA demethylation in promoter CpG islands. In addition, miR-767 targets TET1 and TET3, and overexpression of miR-767 in cancer cells represses TET1 and TET3 and reduces genomic 5-hmC levels [ 150 ]. Collectively, these results indicate that dysregulation of specifi c miRNAs may be causally related to aberrant DNA methylation in cancer.…”
Section: Dna Methylationmentioning
confidence: 74%